Tamarind mem - Badami, Anita Rau (Penguin, 2010)
A beautiful and brilliant portrait of two generations of women. Set in India's railway colonies, this is the story of Kamini and her mother Saroja, nicknamed Tamarind Mem due to her sour tongue. While in Canada beginning her graduate studies, Kamini receives a postcard from her mother saying she has sold their home and is travelling through India. Both are forced into the past to confront their dreams and losses and to explore the love that binds mothers and daughters everywhere